Global Epidemiology of Early-Onset Aortic Aneurysm: Temporal Trends, Risk Factors, and Future Burden Projections - Heng Wang; Yaling Li; Keyi Fan; Taoran Zhao; Keyang Xu; Mayeesha Zahin; Shule Wang; Genmao Cao; Tingting Gao; Xiaohua Jia; Ruijing Zhang; Honglin Dong; et al. (Journal of Epidemiology and Global Health)
Abstract Background Aortic aneurysm has a subtle onset, high rupture mortality, rapid progression in younger individuals, and increasing annual mortality rates. Our study aimed to estimate the global burden and trends of early-onset aortic aneurysm from 1990 to 2021. Methods Participants aged 15–39 years from 204 countries and regions (Global Burdern of Disease, GBD) from 1990 to 2021.The primary assessment indicators include age-standardized death rates (ASDR), age-standardized disability-adjusted life years rates (ASDALYR), annual average percent change (AAPC), attributable risk factor proportions, slope index, concentration index, and predictive model for early-onset aortic aneurysm. Results From 1990 to 2021, the ASDR for aortic aneurysm in adolescents and young adults increased from 0.12 (95% confidence interval [CI] 0.11, 0.14) to 0.13 (0.11, 0.14) per 100,000 population, with an AAPC of 0.08% (-0.08%, 0.25%). The ASDALYR rose from 7.25 (6.52, 8.30) to 7.35 (6.51, 8.37), with an AAPC of 0.07% (-0.09%, 0.23%). Both ASDR and ASDALYR are higher in males than females, with a declining trend in females. Higher Socio-Demographic Index (SDI) countries exhibit higher ASDR and ASDALYR compared to lower SDI countries, with a continuous decline observed in high SDI nations. Smoking remains the top risk factor, with population growth being the primary driver. Models predict a global increase in aortic aneurysm deaths, predominantly among males. Conclusion The overall burden of early-onset aortic aneurysms has exhibited an increasing trend over the last three decades, especially in lower SDI countries. There is an urgent need to develop targeted prevention and control strategies across different regions and countries worldwide.